RNA testing for the diagnosis of acute hepatitis A during the 2017 outbreak in France. Issue 5 (22nd February 2020) - Tram, Julie; Le Baccon‐Sollier, Paul; Bolloré, Karine; Ducos, Jacques; Mondain, Anne‐Marie; Pastor, Patrick; Pageaux, Georges‐Philippe; Makinson, Alain; de Perre, Philippe Van; Tuaillon, Edouard
Abstract: Diagnostic of acute hepatitis A virus (HAV) infection is based on the detection of anti‐HAV IgM without testing for the pathogen itself. We evaluated the usefulness of HAV RNA testing for confirmation of acute hepatitis A and to provide indications about the level of HAV replication in HIV‐positive and HIV‐negative subjects during an unprecedented outbreak of HAV observed in France in 2017. HAV RNA was detected in 38 out of 41 (92.6%) subjects with a clinical diagnosis of acute hepatitis A, whereas nine cases tested positive for anti‐HAV IgM in whom the diagnosis of acute hepatitis A was not retained were found negative for HAV RNA. All subjects in the control group were also tested negative for HAV RNA. HAV viremia was correlated to ALT peak ( r = .64; P < .0001). HIV‐infected patients have similar HAV RNA levels but were less likely to have prolonged international normalized ratio of prothrombin time when compared to the HIV‐uninfected group ( P = .016), suggesting a less severe course of acute hepatitis. HAV RNA was detected in the serum of most of the patients with acute hepatitis A, indicating that the direct detection of HAV can be used to confirm hepatitis A in patients tested positive for anti‐HAV IgM antibodies. Nucleic acid tests should serve more broadly during the diagnosis workup of acute hepatitis A to improve the predictive values of HAV in vitro diagnostic tests and to confirm acute hepatitis A in patients tested positive with IgM with moderate or low S/CO values.